Lack of evidence of viability and infectivity of SARS-CoV-2 in the fecal specimens of COVID-19 patients - Joshi, Madhuri; Mohandas, Sreelekshmy; Prasad, Sharda; Shinde, Manohar; Chavan, Nutan; Yadav, Pragya D.; Lavania, Mallika (Frontiers in Public Health, 2022)
SARS-CoV-2 can be shed in faeces and can enter sewage systems. In order to implement effective control measures and identify new channels of transmission, it is essential to identify the presence of infectious virus particles in faeces and sewage. In this study, we attempt to utilize both molecular techniques and cell culture to find out the infectivity of SARS CoV-2 in the faeces of COVID-19 patients. Our findings exclude out the presence of infectious virus particles, suggesting that fecal-oral transmission is not the main mode of transmission. Larger-scale initiatives are nevertheless required, particularly in light of the emergence of new viral strains.